Nanomaterial Fate in Seawater: A Rapid Sink or Intermittent Stabilization? - Gondikas, Andreas; Gallego-Urrea, Julian; Halbach, Maurits; Derrien, Nicolas; Hassellöv, Martin (Frontiers in Environmental Science, 2020)
Coastal seas and oceans receive engineered nanoparticles that are released from nano-enabled consumer and industrial products and incidental nanoparticles that are formed as byproducts of combustion and friction. The marine environment is often perceived as a rapid sink for particles, because of the high salinity promoting the attachment between particles producing heavy agglomerates that sediment on the seafloor. In this work the effect of seasonal production of extracellular polymeric substances (EPS) on particle stability is tested using seawater collected from the Gullmarn fjord in the winter, spring, and summer. A novel approach is used that is based on light scattering of the bulk particle population for tracking agglomerates and of single particles for tracking particles smaller than approximately 300 nm. Results show that organic particles formed from EPS during algal blooms are capable of stabilizing nanoparticles in marine waters for at least 48 hours. In contrast, particles agglomerate rapidly in the same seawater that has previously been filtered through 0.02 µm pore size membranes. Furthermore, particles with fibrillar shape have been detected using atomic force microscopy, supporting the argument that organic particles from EPS are responsible for the stabilization effect. These results suggest that seasonal biological activity can act as an intermittent stabilization factor for nanoparticles in marine waters.